What makes university students perfectionists? The role of childhood trauma, emotional dysregulation, academic anxiety, and social support. Issue 3 (20th March 2021) - Dobos, Bianka; Piko, Bettina F.; Mellor, David
Abstract : While most studies concentrate on the negative psychological consequences of perfectionism, we know less about its antecedents. This study examined the relationship between adverse childhood experiences, difficulties in emotion regulation, academic anxiety and social support and maladaptive perfectionism among university students. A large sample of 1, 750 students (81% female; M  = 21.6 years, SD  = 4.8) completed an online self‐report survey assessing these constructs. Relative to males, female participants recorded higher scores for difficulties in emotion regulation, perceived social support and debilitating anxiety but not for perfectionism. In line with previous studies, perfectionism was positively related to difficulties in emotion regulation and childhood trauma, with the former being the stronger predictive variable. Debilitating academic anxiety was also a positive but much weaker contributor. In contrast, perceived social support was a significant negative predictor of perfectionism, suggesting that perfectionists can benefit from social connections. Age and gender did not play a role in perfectionism scores. These findings draw attention to the predictive role of emotion regulation and childhood adverse experiences in maladaptive perfectionism and stimulate further research into exploring its association with social support and test anxiety.